An evaluation of venous thromboembolism by whole-body enhanced CT scan for critical COVID-19 pneumonia with markedly rises of coagulopathy related factors: a case series study - Fumihiro Ogawa; Yasufumi Oi; Kento Nakajima; Reo Matsumura; Tomoki Nakagawa; Takao Miyagawa; Takeru Abe; Ichiro Takeuchi (Thrombosis Journal, 2021)
Abstract Background Coronavirus disease (COVID-19) pneumonitis associated with severe respiratory failure has a high mortality rate. Based on recent reports, the most severely ill patients present with coagulopathy, and disseminated intravascular coagulation (DIC)-like massive intravascular clot formation is frequently observed. Coagulopathy has emerged as a significant contributor to thrombotic complications. Although recommendations have been made for anticoagulant use for COVID-19, no guidelines have been specified. Case summary We describe four cases of critical COVID-19 with thrombosis detected by enhanced CT scan. The CT findings of all cases demonstrated typical findings of COVID-19 and pulmonary embolism or deep venous thrombus without critical exacerbation. Two patients died of respiratory failure due to COVID-19. Discussion Previous reports have suggested coagulopathy with thrombotic signs as the main pathological feature of COVID-19, but no previous reports have focused on coagulopathy evaluated by whole-body enhanced CT scan. Changes in hemostatic biomarkers, represented by an increase in D-dimer and fibrin/fibrinogen degradation products, indicated that the essence of coagulopathy was massive fibrin formation. Although there were no clinical symptoms related to their prognosis, critical COVID-19-induced systemic thrombus formation was observed. Conclusions Therapeutic dose anticoagulants should be considered for critical COVID-19 because of induced coagulopathy, and aggressive follow-up by whole body enhanced CT scan for systemic venous thromboembolism (VTE) is necessary.